The "false Eucoila" finally named; Striatovertex a new genus of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) - Schick, Katherine N; Forshage, Mattias; Nordlander, Göran (Zootaxa, 2011)
The new genus Striatovertex is described to accomodate a distinct group of eucoiline wasps (Hymenoptera: Cynipoidea: Figitidae) currently included in the nominate genus Eucoila Westwood, but known among specialists to not belong there for decades. They are characteristically large wasps with reduced wing pubescence, parasitizing dung-breeding Diptera, and are common in North and South America, but also present in Australia and Hawaii. Their diagnostic characters place them in what is currently Ganaspini rather than very close to Eucoila in Eucoilini, and this has been confirmed by earlier phylogenetic analyses. Diagnostic and other distinctive characters are reviewed, and thirteen new combinations are made for species belonging to this group.